2023
DOI: 10.7759/cureus.39444
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Crevicular Blood Glucose as a Novel Method for Screening Diabetes Mellitus in Periodontally Compromised Patients

Abstract: Introduction: Patients with periodontitis are significantly more likely to have undetected diabetes mellitus (DM). Self‑monitoring devices like glucometers provide a simple method for rapid monitoring of the glucose level in blood by utilizing a blood sample from the finger, but this method requires puncturing to obtain blood. Bleeding from the gingival sulcus, obtained during oral hygiene examination, can be utilized for screening DM patients. Therefore, this study was performed with the aim of determining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…16 studies have reported their outcomes in mg/dl while two in mmol/l which were converted to mg/dl by the authors. The highest and lowest mean values recorded from GCB was 243.27 and 156.07 mg/dl in the DM group and 118.76 and 90.08 mg/dl in the non-DM group respectively [ 12 , 25 35 , 37 , 40 , 41 , 43 45 ]. Two of the studies have found statistically significant differences between GCB and CB values ( p = 0.001) [ 33 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…16 studies have reported their outcomes in mg/dl while two in mmol/l which were converted to mg/dl by the authors. The highest and lowest mean values recorded from GCB was 243.27 and 156.07 mg/dl in the DM group and 118.76 and 90.08 mg/dl in the non-DM group respectively [ 12 , 25 35 , 37 , 40 , 41 , 43 45 ]. Two of the studies have found statistically significant differences between GCB and CB values ( p = 0.001) [ 33 , 37 ].…”
Section: Resultsmentioning
confidence: 99%